Two-year history of lymphadenopathy and fever caused by Bartonella henselae in a child - Maria, Helga Kaiser Sanches de; Gazzoli, Emily; Drummond, Marina Rovani; Almeida, Amanda Roberta de; Santos, Luciene Silva dos; Pereira, Ricardo Mendes; Tresoldi, Antonia Terezinha; Velho, Paulo Eduardo Neves Ferreira (Revista do Instituto de Medicina Tropical de São Paulo, 2022)
We report the case of a 6-year-old boy that presented with enlarged lymph nodes on his neck. He complained of tiredness and discouragement, which worsened during feverish periods. There were no relevant laboratory test abnormalities and serological tests were not reactive. Bartonella henselae DNA was detected by species-specific nested polymerase chain reaction. After treatment, the patient progressed with no fever or lymphadenopathy. Bartonellosis is a group of infectious diseases caused by bacteria of the genus Bartonella. This case report is a useful reminder to clinicians that long-term fever of unknown origin can be related to B. henselae infection, even if the specific serology is not reactive.